MODERN PROBLEMS OF MEDICAL AND PHARMACEUTICAL CARE FOR OCCUPATIONAL DISEASES - Петров, Андрей Георгиевич; Семенихин, Виктор Андреевич; Хорошилова, Ольга Владимировна; Филимонов, Сергей Николаевич; Черных, Наталья Степановна (Medicine in Kuzbass, 2022)
Comprehensive medical and pharmaceutical studies of the problem of occupational morbidity in Kuzbass were not carried out enough, while the results obtained will contribute to solving the problem of occupational diseases (OD), maintaining the health of the working population.The purpose of the study is to study the provision of medical and pharmaceutical care for occupational diseases.Material and research methods. When studying the provision of medical and pharmaceutical care in the case of PZ, the following methods were used: marketing, graphic, sociological, content analysis.Results. The main identified problems are: lack of a system of pharmaceutical care for patients with PD; lack of specialists with pharmaceutical education in the structure of the occupational medicine service; not implemented function of the pharmacy organization (pharmacy) to serve patients with PD; waste of health care resources.Conclusion. A generalized form of reflection of all the mechanisms of interaction between pharmacy and medical organizations in the work to rationalize medical and pharmaceutical care for occupational diseases should be individual interaction with consumers; control over the use of medicines in accordance with the prescribed course therapy; identification and prevention of possible difficulties in drug care; timely informing the attending physician about the manifestation of the undesirable effect of drugs; teaching the principles of responsible self-treatment.
Keywords: medical and pharmaceutical care; occupational diseases; occupational medicine